Effect of pH on the thermostability and redox properties of cytochrome c552 from Wolinella succinogenes - Mordido, Vitor H.; Carepo, Marta S. P.; Cordas, Cristina M.; Paul, Navendu; Simon, Jörg; Moura, Isabel; Pauleta, Sofia R. (Frontiers in Chemical Biology, 2024)
Cytochrome c552 from Wolinella succinogenes is one of the few examples of a low reduction potential class I c-type cytochrome with a mixture of high/low spin state populations observed in its visible spectrum. Analysis of its structural model suggests that the heme is Met/His coordinated and highly solvent-exposed. This supports the hypothesis that it is the solvent accessibility of the propionate groups that controls the reduction potential of small c-type cytochromes. The visible spectra obtained at different pH values reveal the presence of a protonable group with a pKa of 7.3, which also influences the reduction potential of this small cytochrome c552 (Em 0' of 97 ± 5 mV, pH 7.0) and can be either an H2O/OH -group distantly coordinating the heme iron, or one of the propionate groups. The thermostability of cytochrome c552 has been studied by circular dichroism and differential scanning calorimetry, indicating a highly stable protein at pH 5-7 (90 ºC to 77 ºC).